Efficacy of preemptive analgesia treatments for the management of postoperative pain: a network meta-analysis - Xuan, Chengluan; Yan, Wen; Wang, Dan; Li, Cong; Ma, Haichun; Mueller, Ariel; Chin, Vanessa; Houle, Timothy T.; Wang, Jingping (British journal of anaesthesia : BJA, 2022)
Preemptive analgesia may improve postoperative pain management, but the optimal regimen is unclear. This study aimed to compare the effects and adverse events of preemptive analgesia on postoperative pain and opioid consumption. In this network meta-analysis, 19 preemptive analgesia regimens were compared. Two authors independently searched databases, selected studies, and extracted data. Primary outcomes were the intensity of postoperative pain and opioid consumption. Secondary outcomes included the time to first analgesia rescue and incidence of postoperative nausea or vomiting (PONV). In total, 188 studies were included (13 769 subjects). Ten of 19 regimens reduced postoperative pain intensity compared with placebo, with mean differences 100-point scale ranging from −4.79 (95% confidence interval [CI]: −8.61 to −0.96.) for gabapentin at 48 h to −21.99 (95% CI: −36.97 to −7.02) for lornoxicam at 6 h. Eight regimens reduced opioid consumption compared with placebo, with mean differences ranging from −0.48 mg (95% CI: −0.89 to −0.08) i.v. milligrams of morphine equivalents (IMME) for acetaminophen at 12 h to −2.27 IMME (95% CI: −3.07 to −1.46) for ibuprofen at 24 h. Five regimens delayed rescue analgesia from 1.75 (95% CI: 0.59–2.91) h for gabapentin to 7.35 (95% CI: 3.66–11.04) h for epidural analgesia. Five regimens had a lower incidence of PONV compared with placebo, ranging from an odds ratio of 0.22 (95% CI: 0.11–0.42) for ibuprofen to 0.59 (95% CI: 0.40–0.87) for pregabalin. Use of preemptive analgesia reduces postoperative pain, opioid consumption, and postoperative nausea or vomiting, and delays rescue analgesia. PROSPERO CRD42021232593.